Особливості стратегічного управління на промислових підприємствах з надання ремонтних послуг - Захарченко, Віталій Іванович (НТУ "ХПІ", 2015)
Обґрунтовано актуальність дослідження ринку ремонтних послуг та особливостей стратегічного управління підприємствами, що функціонують на ньому. Проаналізовано ринок ремонтних послуг. Визначено сучасний стан та тенденції розвитку промислових підприємств, що функціонують на ньому, та їх споживачів. Виявлено особливості стратегічного вибору промислових підприємств з надання ремонтних послуг. Зроблено висновки на основі отриманих результатів.

The research relevance of the repair services market has been discovered. The study importance of strategic management features on the repair services industrial enterprises has been substantiated. The theoretical bases of the strategic management and strategies delivery have been explored. Thе repair services market has been analyzed. The modern state and development trends of the industrial enterprises that operate on it and their customers have been defined. The strategic choice features of repair services industrial enterprises have been identified. The need to incorporate in strategic management this enterprises of the opportunities such as focus on more profitable customers, use of foreign target market segment, partnership cooperation establishing with competitors, provision of services of innovative content. The conclusionsbased on the results obtained have been made.
Features of strategic management on the repair services industrial enterprises
Keywords: база техніко-технологічна; обладнання технологічне; устаткування; монтаж машин